Tranformasi Perpustakaan IPDN Melalui Kerja sama dengan Perpusnas RI dalam Penguatan Sumber Daya Manusia, Teknologi Informasi, dan Infrastruktur - Nur Safitri, Arroyya; Josephine Wattimena, Anne; Nursanti Rukmana, Evi; Silvana Rachmawati, Tine (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study examines the impact of collaboration between the Institute of Domestic Government (IPDN) Library and the National Library of Indonesia (Perpusnas) in improving the capacity of Human Resources (HR), Information and Communication Technology (ICT), and the development of IPDN library infrastructure. Using a qualitative approach with a case study, this research collected data through in-depth interviews with officials and staff involved in the implementation of the collaboration. The results show that the collaboration that began in 2019 has brought significant positive impacts, including the improvement of librarian competencies through training and certification programs, the integration of the INLISLite digital library management system, as well as the development of physical and digital infrastructure. The collaboration has also enabled wider access to digital information resources through platforms such as Indonesia OneSearch (IOS) and Ipusnas. However, challenges such as long-distance communication constraints and a drastic decline in the number of physical visitors to the IPDN central library were also identified. The decline in physical visits was attributed to the ease of access to digital collections, the existence of faculty libraries, and mobile library services. Nonetheless, this collaboration has successfully improved the operational efficiency and service quality of the IPDN library, making it more responsive to user needs in the digital age. This research suggests periodic evaluation of library usage patterns and the development of innovative strategies to re-attract physical visitors, while continuing to expand the reach of digital services. Thus, IPDN Library can continue to adapt to technological developments and user needs, making it more relevant and effective in supporting the education and research process at IPDN.